Flow resistance prediction in high-gradient streams - Yochum, Steven Edward, author; Bledsoe, Brian P., advisor; Rathburn, Sara L., 1962-, committee member; Watson, Chester C., committee member; Wohl, Ellen E., 1962-, committee member (Colorado State University. Libraries, 2010)
Flow resistance measurements were collected on high-gradient streams in the Fraser Experimental Forest, Colorado, for bankfull through low flows using Rhodamine WT dye tracing, ground-based LiDAR scans, and laser theodolite surveying of longitudinal profiles and below-water features. A dataset of 59 resistance measurements was collected on fifteen reaches with instream wood present in varying densities. Values of Manning's n ranged from 0.05 to 0.52, and Darcy-Weisbach ƒ varied from 0.28 to 56. All measurements indicated subcritical reach-average conditions, with Froude numbers ranging from 0.15 to 0.78. Relative grain submergence (R/D84) was a poor predictor of flow resistance while relative bedform submergence, defined as the ratio of depth or hydraulic radius to the standard deviation of the residuals of a bed profile regression (hm/σz, R σz), explained up to 76 and 80 percent of the variance of n and ƒ, respectively. Both clasts and instream wood contribute to bed variability; steps are heightened by wood lodging among the clast steps. Hence relative bedform submergence captures the combined influence of wood and clasts, which contribute both form and spill resistance. Relative bedform submergence is less effective for prediction in reaches with substantial non-step-forming instream wood and in steep channels. In the steepest reaches, with slopes over about 18 percent, the data indicate a shift towards a skimming regime with a partial submergence of bedforms and a threshold reduction in flow resistance. Three-dimensional measures of geometric variability were explored, to assess the correlation of flow resistance with higher-order spatial variation due to composite effects of bedforms, large clasts, and instream wood. With the exclusion of bank effects, a normalized variable (ha3/σz3) explained 77 and 81 percent of the variance of n and ƒ, respectively. Multivariate regression models with variables describing bedforms, bankforms, and instream wood explained 87 percent of the variance of n and ƒ. On average, flow resistance due to bedforms (form and spill) are the greatest contributor to overall flow resistance in these high-gradient streams, followed by form resistance generated by bankforms, and lastly, by form resistance induced by non-step instream wood.
Zip file contains data spreadsheet.
Keywords: velocity; step pool; Manning's N; flow resistance; Darcy-Weisbach ƒ; cascade; Streamflow -- Colorado -- Fraser Experimental Forest; Stream measurements -- Colorado -- Fraser Experimental Forest; Channels (Hydraulic engineering) -- Colorado -- Fraser Experimental Forest; Frictional resistance (Hydrodynamics) -- Colorado -- Fraser Experimental Forest; Cascades (Fluid dynamics) -- Colorado -- Fraser Experimental Forest; Fraser Experimental Forest (Colo.)